The Impact Of Delaying Elective Surgeries On Patient Safety During Covid-19: Literature Review - Ulya Serly Amrillah (International Journal of Health Engineering and Technology, 2026)
The COVID-19 pandemic has had a major impact on the global healthcare system, including the postponement of elective operations due to limited resources and efforts to prevent the transmission of the virus. Globally, more than 28 million operations were postponed, including in Indonesia. Delays have an effect on patient safety because they risk having a serious impact on patients. This study aims to understand the impact of delaying elective surgeries on patient safety during the COVID-19 pandemic. The design of this research is a literature review. Searching for articles through the Pubmed, Science Direct, and Google Scholar databases (2020-2025) using the keywords "patient safety" AND "elective surgery" OR "delay elective surgery" AND "covid elective surgery" OR "delay covid elective surgery". Data are extracted based on objectives, research design, research samples, research locations, and findings. The total number of article findings was 844, but only 8 articles met the inclusion criteria. The impact of delay on patient safety is classified into three main categories: (1) Physical health includes decreased physical health score, increased pain, increased risk of falling, and increased weight gain (average 4 kg); (2) Mental health includes anxiety, depression, frustration, and adverse psychological effects; (3) Delay in the recovery process. The delay in elective surgeries during COVID-19 has an impact on patient safety, namely physical health, mental health, and delays in the patient's recovery process.